Background parenchymal enhancement and fibroglandular tissue on breast MRI in women with high genetic risk: Are changes before and after risk-reducing salpingo-oophorectomy associated with breast cancer risk?. Issue 109 (December 2018) - Bermot, Cécile; Saint-Martin, Caroline; Malhaire, Caroline; Sebbag-Sfez, Delphine; Mouret-Fourme, Emmanuelle; Carton, Matthieu; Thibault, Fabienne E.
Highlights: Post-RRSO BPE decrease was associated with a higher risk of later breast cancer. Initial moderate vs minimal BPE correlated with higher post-RRSO breast cancer risk. Initial dense vs fatty FGT correlated with higher post-RRSO breast cancer risk. High initial BPE could be a distinctive risk marker from post-RRSO BPE reduction. Abstract: Background: Parenchymal enhancement and fibroglandular tissue on breast MRI in women with high genetic risk: are changes before and after risk-reducing salpingo-oophorectomy associated with breast cancer risk? Objective: To evaluate changes in the level of background parenchymal enhancement (BPE) and amount of fibroglandular tissue (FGT) on breast MRI before and after risk-reducing oophorectomy (RRSO), and to determine whether these changes correlate with ultimate breast cancer risk. Materials and methods: The cohort included 146 women with high genetic risk who had undergone pre- and post-RRSO breast MRI. BPE level and FGT amount were retrospectively graded according to BI-RADS classification. Initial values and changes were compared in women with or without later breast cancer after RRSO. Hazard ratios (HR) were estimated using Cox univariate models. Results: Patients with initial moderate (BI-RADS C category) BPE had a higher risk of subsequent breast cancer of HR = 3.9 (95% CI [1.1–14.3]; p = 0.04) compared to patients with initial minimal (BI-RADS A) BPE. A categorical BPE decrease after RRSO, versus no change, was associated with a higher cancer risk (HR 2.2, 95% CI [1.04–4.8]; p = 0.04). Initially dense (BI-RADS 3 category) FGT correlated with an increased cancer risk compared to fatty (BI-RADS 1 category) parenchyma (HR 8.3, 95% CI [1.1–64]; p = 0.04). After RRSO, there was a trend for higher cancer risk related to a categorical FGT decrease (HR 2.3, 95% CI [0.9–35.4]; p = 0.06). Conclusion: Patients in whom BPE decreases after RRSO might be at higher risk of subsequent breast cancer compared to patients with stable BPE. This finding is consistent with the concept of increased risk associated with high initial BPE, which could be of higher clinical relevance than post-RRSO BPE reduction. A similar trend was observed with high initial FGT.